Integrasi Filsafat, Manusia, dan Pendidikan dalam Perspektif Islam: Tinjauan Ontologis, Epistimologis, dan Aksiologis (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2025)
In an effort to understand the nature of existence and the purpose of education, humans continually ponder fundamental questions about reality, knowledge, and life's values. Philosophy appears as a light that illuminates the darkness of these questions, offering a profound and systematic framework for thought. However, from an Islamic perspective, this search for truth does not rely solely on reason but is harmoniously integrated with Divine revelation. Islamic ontology places God as the source of all reality, its epistemology unites reason and revelation in the pursuit of knowledge, while axiology guides all educational actions and goals toward the formation of pious and noble individuals. This symbiotic integration gives rise to a transformative educational paradigm that not only fosters intellectual intelligence but also humanizes and purifies the soul, thus producing a holistic generation that contributes to the well-being of humanity. This paradigm aligns Islamic education with global realities, prioritizing a balance between worldly and otherworldly knowledge, and emphasizing moral and spiritual development as integral parts of a more holistic and sustainable education.